Current views on etiology, diagnosis, epidemiology and gene therapy of maturity onset diabetes in the young - Dzhemileva, Lilya U.; Zakharova, Elena N.; Goncharenko, Anna O.; Vorontsova, Maria V.; Rumyantsev, S. A.; Mokrysheva, Natalia G.; Loguinova, Marina Y.; Chekhonin, Vladimir P. (Frontiers in Endocrinology, 2025)
MODY, or maturity-onset diabetes of the young, is a group of monogenic diseases characterized by autosomal dominant inheritance of a non-insulin-dependent form of diabetes that classically manifests in adolescence or in young adults under 25 years of age. MODY is a rare cause of diabetes, accounting for 1% of all cases, and is often misdiagnosed as type 1 or type 2 diabetes. It is of great importance to accurately diagnose MODY, as this allows for the most appropriate treatment of patients and facilitates early diagnosis for them and their families. This disease has a high degree of phenotypic and genetic polymorphism. The most prevalent forms of the disease are attributed to mutations in three genes: GCK (MODY 2) and (HNF)1A/4A (MODY 3 and MODY 1). The remaining MODY subtypes, which are less prevalent, have been identified by next generation sequencing (NGS) in the last decade. Mutations in the GCK gene result in asymptomatic, stable fasting hyperglycemia, which does not require specific treatment. Mutations in the HNF1A and HNF4A genes result in pancreatic β-cell dysfunction, which in turn causes hyperglycemia. This often leads to diabetic angiopathy. The most commonly prescribed drugs for the treatment of hyperglycemia are sulfonylurea derivatives. Nevertheless, with advancing age, some patients may require insulin therapy due to the development of resistance to sulfonylurea drugs. The strategy of gene therapy for monogenic forms of MODY is still an experimental approach, and it is unlikely to be widely used in the clinic due to the peculiarities of MODY structure and the high genetic polymorphism and clinical variability even within the same form of the disease. Furthermore, there is a lack of clear gene-phenotypic correlations, and there is quite satisfactory curability in the majority of patients. This review presents the main clinical and genetic characteristics and mutation spectrum of common and rarer forms of MODY, with a detailed analysis of the field of application of AVV vectors in the correction of hyperglycemia and insulin resistance.